PENGARUH PERSEPSI KEUANGAN DAN PENGELOLAAN KEUANGAN TERHADAP PERENCANAAN KEUANGAN: PERAN MEDIASI LITERASI KEUANGAN - Alfa Santoso Budiwidjojo Putra; Evi Dewi Kusumawati; Dewi Kartikasari (Fakultas Ekonomi dan Bisnis, Universitas Wiraraja Madura, 2024)
This study aims to analyze the influence of financial perception and financial management on financial planning with financial literacy as a mediating variable. The problem investigated is how financial perception, financial management, and financial literacy affect individual financial planning. This study uses a quantitative approach with a survey method on subjects involved in personal financial management. Data was collected through online questionnaires distributed to active adult financial managers. The data was then analyzed using Structural Equation Modeling (SEM) with the help of SmartPLS software. The results show that financial perception has a significant effect on financial planning, financial management has a significant effect on financial planning, and financial literacy has a significant effect on financial planning. Furthermore, financial literacy was proven to mediate the influence of financial perception and financial management on financial planning. The conclusion of this study is that financial perception, financial management, and financial literacy play an important role in improving individual financial planning. Financial literacy has been proven to be a mediating factor that strengthens the relationship between financial perception, financial management, and financial planning. Practical implications and recommendations for future research are also discussed.